13 Gene Expression Pattern of Arabidopsis EXPB1, a Nonallergenic Homologue of Grass Group 1 Pollen Allergens - Bhalla, Prem (World Allergy Organization Journal, 2012)
BACKGROUND: Grass pollen allergy is one of the most common allergies worldwide. Group I allergens constitute the major allergenic component of grass pollen with more than 85% of grass pollen allergic patients showing IgE reactivity. These are highly immunologically cross-reactive glycoproteins specifically expressed in pollen of all grasses. Alignments of the amino-acid sequences of grass group I allergens derived from diverse grass species reveal up to 95% homology. It is therefore likely that these molecules share a similar biological function. METHODS: RT-PCR analysis, In situ hybridisation, Promoter-GFP construct design, plant transformation and analysis of transgenic plants. RESULTS: Sequence comparison has identified a homologue (β-expansin clone At2g20750 or EXPB1) in Arabidopsis of the Cyn d 1 gene. The EXPB1 protein is 42% similar to the Cyn d 1 protein. This gene represents a member of a small multigene family in Arabidopsis. RT-PCR analysis showed expression only in floral not vegetative tissues. In situ hybridisation using 150 bp region of the 3′ UTR of the Arabidopsis gene as probe showed specific expression in mature Arabidopsis pollen. We further cloned the promoter region for the Arabidopsis EXPB1 and prepared and GFP fusion constructs. These constructs were then introduced in to Arabidopsis plants by floral dip method. GFP-promoter fusions showed high level of expression in tri-cellular pollen. CONCLUSIONS: Our study provides evidence that EXPB1, a non-allergenic homologue of grass group 1 pollen allergens, gene is expressed in mature pollen.